Meaning in the semantic theory of Mikhail V. Nikitin and in cognitive grammar of Ronald W. Langacker - Kharitonchik Zinaida A. (Južnoslovenski Filolog)
The paper is focused on common and different aspects of two leading semasiological theories of today - the theory of the Russian semasiologist M. V. Nikitin and that of the American cognitive linguist R. W. Langacker. Both authors view meaning as a complex psychic phenomenon whose formation is affected by numerous factors - social, cultural, psychological, situational, etc. The paper focuses on significant, but not identical aspects of these theories, which represent their major distinctive features - sources of meaning and basic structures of consciousness according to M. V. Nikitin, as well as the actualization of components of the construed meaning under the impact of specificity/schematics, focusing, prominence and perspective as factors which affect the construal according to R. W. Langacker. It becomes evident that they do not so much contradict as complement each other, revealing such essential facets of meaning as its formation and functioning.